PENINGKATAN PENGETAHUAN PENDEWASAAN USIA PERKAWINAN MELALUI PEER GROUP EDUCATION PADA REMAJA DI PIK-R KAPAS CIREBON - Omay Rohmana; Ati, Ati Siti Rochayati (P3M Universitas Aisyiyah Surakarta, 2024)
Indonesia teenager’s population in 2021 has 66,893,500. The teenager’s knowledge about reproductive health is inadequate and it’s the reason for the first marriage Indonesian women age still in 19.8 years. Pusat Informasi Dan Konsultasi Remaja (PIK-R) Kapas RW 03 Kedung Mendeng, Cirebon has 165 registered members, but they have never been given education for family life preparation Marriage Age Maturity (PUP). The aim is increasing the teenager’s knowledge about family life preparation Marriage Age Maturity (PUP). The method is peer group education, with 20 participants, consisting of 5 peer educators and 15 participants. The results are the participant’s pre-test was 34 average score and the post-test was 65 average score, there was an increase on the average score in 31 or 90%. There was a significant change in teenager’s knowledge after being given peer group education for Marriage Age Maturity (PUP) with p value = 0.000 < 0.05. Teenager’s Knowledge of Marriage Age Maturity (PUP) at PIK-R Kapas Cirebon increased after attending peer group education. Teenagers at PIK-R Kapas must spread out Marriage Age Maturity (PUP) information to the others using this method